Emission-Line Fluxes of Northern Planetary Nebulae. (16th February 2015) - Aksaker, N.; Yerli, S. K.; KÄ±zÄ±loÄŸlu, Ãœ; Atalay, B.
Abstract We present long slit spectrophotometric emission line fluxes of bright and extended (< 5 arcsec in diameter) planetary nebulae (PNe), selected from a catalogue with suitable equatorial coordinates for northern hemisphere. In total, 17 planetary nebulae have been chosen and observed in 2008â€"2010. To measure absolute fluxes, broad slit sizes, ranging from 3.5 to 7.5 arcsec were used and thus equivalent widths (EW) of all observable emission line fluxes were also calculated. Among 17 planetary nebulae observed, line flux measurements of 12 of them were made for the first time. This work also aims to extend the sky coverage of emission line flux standards in northern hemisphere (52 planetary nebulae in southern hemisphere; 6 planetary nebulae in northern hemisphere). Electron temperatures and densities, and chemical abundances of these planetary nebulae were also calculated in this work. These data are expected to lead the photometric or spectrometric further work for absolute emission line flux measurements needed for H ii regions, supernova remnants etc.